Eastern enlargement and EU labour markets perceptions, challenges and opportunities - Boeri, Tito 1958-; Brücker, Herbert (IZA, 2001)
This paper summarises the key findings of a recent study on the impact of Eastern Enlargement of the European Union (EU) on labour markets in the current Member States. The study focuses on three main channels, along which enlargement may affect labour markets in the EU, namely i) trade, ii) foreign direct investment, and iii) migration. A main conclusion of the study is that trade and capital movements are very unlikely to lead to an equalisation of factor prices. Thus, strong economic incentives to migration are bound to be present well beyond the date of accession. We estimate the migration potential associated with Eastern enlargement drawing on a time series model of immigration to Germany, which allows to estimate the long-term equilibrium migration potential, as well as the speed of adjustment at which the potential takes place
Keywords: Europäische Union; Beschäftigungsniveau; Einwanderung; Internationaler Arbeitsmarkt; Mitgliedsstaaten; Welthandel; Arbeitsmarkt / Internationale Arbeitsmobilität / EU-Staaten; EU-Erweiterung / Osteuropa